Tourism Governance with Culinary Cognitive Images Base in the City of Pare-Pare - Nur Salam (Universitas Muhammadiyah Gorontalo, 2021)
Culinary tourism is a new thing in the repertoire of interesting and distinctive dishes and tourism. The food is in the form of food that is usually eaten and processed by local residents, and is not consumed outside the area. The purpose of this Reseach to know the tourism governance with culinary cognitive images based in the City of Pare-Pare. The population in this study is tourists Parepare City Destination. The sample was taken as many as 100 respondents from tourist Parepare City Destination. The analytical tool in this research is Descriptive Analysis, Instrument Test, Multiple Regression Analysis, Significance Test (t test), and Model Accuracy Test. The results showed that cognitive Culinary image has a significant positive effect on the interest of tourists visit Parepare City Destination, and affective Culinary image have a significant positive effect on the interest of tourist visit Parepare City Destination. Both variables are also influential together on the interest of tourists visit Parepare City Destination. Based on the result of this research, the management of Parepare City Destination can increase the interest of tourist visit by increasing the cognitive Culinary image variable and the affective Culinary image variable, because the increasing of both variables is increasing the tourist visit.